ChemInform Abstract: Two New Triterpenoids from Lycopodium japonicumThunb. Issue 15 (April 2015) - Wang, Xiaojing; Yu, Dequan; Yu, Shishan
Abstract: isolation and characterization of two new serratene‐type triterpenoids (I) and (II)